(untitled) (Pedagogy of Higher and Secondary Education, 2016)
Tatarnikova A. A. Pedagogical conditions of professional competence development of music students in Arts Management. This article comprises the substantiation of the pedagogical conditions of professional competence development of music students in Arts Management based on the analysis of the conceptual approaches of foreign and Ukrainian scientists to educational programmes’ research in Arts Management, as well as the modernisation of professional music education system. The importance of the vocational training of music students who are to become Arts Managers is also demonstrated in the article. The future specialists have to obtain the leading technologies of Arts Managements, i.e. promotion of Arts product, concert administration, information support of Arts product and performer’s creative work, Internet promotional campaigns, operating a blog in social networks, collaboration with sponsors (fundraising, patronage, and charity), etc. It is emphasized that the analysis of educational curricula and programmes, as well as the empirical study on the levels of professional competence of musicians-alumni in Arts Management in Ukraine conclusively confirm the fact that the intentional development of the alumnus individuality like a professional Arts Manager in the field of musical art until now has not been provided in a proper manner. Therefore, the didactical potential of the main principles and means of competency-based and concentrated-on-student approaches to its organisation and the results’ quality evaluation is reached. It is also proved that the development of the professional competence of music students in Arts Management while receiving their degree in Music will take place more effectively if some special pedagogical conditions are managed to be created during the education process. These conditions are the enrichment of contents of Arts education with the theoretical questions of Arts Management, the maintenance of the individual research activities of students on gaining the main technologies of Arts Management, the pedagogical support of individual professional self-development of students as Arts Managers in the field of the Art of Music, and the motivation of students in their participation in different projects based on the artistic and creative activities. It is shown that the means of the concentrated-on-student approach, like the principles of humanization, individualization, personalization, dialogization, scientificity, occupational mobility, contextuality of education, diversification of artistic education, its universality, adequacy to its contents, forms and methods of contemporary targets and functions of musician-specialist as an Arts Manager, the combination of pedagogical facilitation and the development of initiatives and leadership of the members of the social and cultural environment, the problemacity and situatedness of education, its close relation to the Arts Management practice, contribute to the practical realization of the indicated pedagogical conditions.